Multiple wavelength laser utilizing hybrid erbuim and brillouin gains in dispersion compensating fiber - Ajiya, Mohammed (2010)
This dissertation presents experimental design and development of multiwavelength fiber laser sources utilizing hybrid erbium and Brillouin gains in dispersion compensating fiber. Four laser designs have been successfully demonstrated. Also presented is a simple method of stimulated Brillouin scattering threshold (SBS) reduction. Highly stable multiwavelength Brillouin/erbium fiber laser (MWBEFL) in which the cavity is formed by a virtual mirror, where the oscillating modes are reflected back into the laser cavity by SBS effect rather than by a physical reflector is demonstrated. The issue of low tuning range associated with such laser configurations was successfully resolved. Tuning range of 39 nm from 1527 to 1566 nm, which is only limited by the amplification bandwidth of the erbium gain was successfully achieved. At maximum pumping powers, four channels that are rigidly separated by 0.08 nm (10 GHz) and where each has power above 0 dBm has been demonstrated. Simple method of SBS threshold reduction was demonstrated. The BP signal was recycled back into the fiber thereby increasing the total gain in the fiber and thus SBS threshold was reduced. In a 5 km long fiber, the proposed method reduced SBS threshold by over 48%, from 16.5 mW to 8.5 mW of the input signal. The Brillouin Stokes generated in the 5 km fiber has a peak power of 9.2 dBm against 4.3 dBm measured using the conventional technique. Similarly, the results obtained from the various lengths of tested fibers, proved that the proposed technique significantly reduced the SBS threshold value and improved the level of the Brillouin Stokes signal power. Two structures of MWBEFL incorporating the SBS threshold reduction technique were also proposed. In one structure, unidirectional propagation of both the Brillouin Stokes and the Brillouin pump signals was allowed through the erbium amplifier while in the other, bidirectional propagation of the two signals are forced through the erbium gain.The unidirectional amplifier configuration provides greater tuning range of 46.8 nm,against 23 nm provided by the bidirectional configuration at the same pumping powers. On the other hand, the bidirectional amplifier configuration provides 13 output channels against only 6 output channels obtained from the unidirectional amplifier configuration under maximum pumping powers. The channels output power however remained lower than 0 dBm in both cases. An enhanced structure of MWBEFL that provided flawless tuning range and high channels power was also demonstrated. At maximum pumping powers, up to seven output channels that can broadly be tuned over 35 nm, are demonstrated. Wavelength tunability is also limited by the amplification bandwidth of the erbium amplifier employed. Each of the initial four channels has peak power above 1.6 dBm with the first and seventh channels having a peak power of 8.19 dBm and -8.30 dBm respectively. After an observation period of one hour, the average power fluctuations by all the seven channels is only 1.47 dB with average wavelength shifts of 0.007 nm.